Role of the non‐invasive imaging techniques in monitoring and understanding the evolution of brain edema. Issue 5 (28th May 2021) - Obenaus, Andre; Badaut, Jérôme
Abstract: Human brain injury elicits accumulation of water within the brain due to a variety of pathophysiological processes. As our understanding of edema emerged two temporally (and cellular) distinct processes were identified, cytotoxic and vasogenic edema. The emergence of both types of edema is reflected by the temporal evolution and is influenced by the underlying pathology (type and extent). However, this two‐edema compartment model does not adequately describe the transition between cytotoxic and vasogenic edema. Hence, a third category has been proposed, termed ionic edema, that is observed in the transition between cytotoxic and vasogenic edema. Magnetic resonance neuroimaging of edema today primarily utilizes T2‐weighted (T2WI) and diffusion‐weighted imaging (DWI). Clinical diagnostics and translational science studies have clearly demonstrated the temporal ability of both T2WI and DWI to monitor edema content and evolution. DWI measures water mobility within the brain reflecting cytotoxic edema. T2WI at later time points when vasogenic edema develops visualizes increased water content in the brain. Clinically relevant imaging modalities, including ultrasound and positron emission tomography, are not typically used to assess edema. In sum, edema imaging is an important cornerstone of clinical diagnostics and translational studies and can guide effective therapeutics manage edema and improve patient outcomes.